#SportToo: Implications of and Best Practice for the #MeToo Movement in Sport - Abrams, M.; Bartlett, M. L. (Journal of Clinical Sport Psychology, 2019)
The #MeToo movement has brought long needed attention to the epidemic of sexual assault and sexual violence. In the world of sports, the need to prevent and address such acts requires individuals with training in clinical, forensic and sport psychology. These professionals must have particular understanding of the dynamics of sexual violence within the athletic and sport culture. This paper serves to highlight context-specific approaches to pertinent identification and treatment issues. An overview of sexual abuse victim and perpetrator identification will be offered. In addition to the introduction of risk assessment and recommendation of comprehensive prevention programming, treatment needs in the athletic context will be explored. Group-level interventions currently being utilized will be reviewed, recommended topic areas to be covered in protocols will be enumerated and suggestions for systemic and cultural change in the sport domain will be offered.